In silico Approaches for the Design and Optimization of Interfering Peptides Against Protein–Protein Interactions - Hashemi, Zahra Sadat; Zarei, Mahboubeh; Fath, Mohsen Karami; Ganji, Mahmoud; Farahani, Mahboube Shahrabi; Afsharnouri, Fatemeh; Pourzardosht, Navid; Khalesi, Bahman; Jahangiri, Abolfazl; Rahbar, Mohammad Reza; Khalili, Saeed (Frontiers in Molecular Biosciences, 2021)
Large contact surfaces of Protein-Protein Interactions (PPIs) remain to be an ongoing issue in the discovery and design of small molecule modulators. Peptides are intrinsically capable of exploring larger surfaces, stable, and bio-available, therefore bear a high therapeutic value in fight against various diseases, including cancer, infectious diseases, and neurodegenerative diseases. Given these promising properties, a long way has been covered in the field of targeting PPIs via peptide design strategies. In silico tools have recently become an inevitable approach for the design and optimization of these interfering peptides. Various algorithms have been developed to scrutinize the protein-protein interaction interfaces. Moreover, different databases and software tool have been created to predict the peptide structures and their interactions with target protein complexes. High throughput screening of large peptide libraries against PPIs, “Hot spot” identification, structure based and Off-structure approaches of peptide design, 3D peptide modeling, peptide optimization strategies like cyclization, and peptide binding energy evaluation are among the capabilities of in silico tools. In the present study, the most recent advances in the field of in silico approaches for the design of interfering peptides against PPIs will be reviewed. The future perspective of the field and its advantages and limitations will also be pinpointed.